Emotions During Sexual Activity: Differences Between Sexually Functional and Dysfunctional Men and Women - Nobre, Pedro (2006)
Abstract The present study investigated the differences in emotional response to automatic thoughts presented during sexual activity between sexually functional and dysfunctional men and women. A total of 376 participants (160 women and 120 men without sexual problems and 47 women and 49 men with a DSM-IV-TR diagnosis of sexual dysfunction) completed the Sexual Modes Questionnaire (SMQ male and female versions; P. J. Nobre & J. Pinto-Gouveia, 2000) and measures of sexual functioning: The International Index of Sexual Function (IIEF; R. C. Rosen et al., 1997), and The Female Sexual Function Index (FSFI; R. C. Rosen et al., 2000). The SMQ is a combined measure constituted by three interdependent subscales: Automatic Thought subscale (AT), Emotional Response subscale (ER), and Sexual Response subscale (SR). Emotions were assessed by the ER subscale, where participants endorsed emotional reactions (worry, sadness, disillusion, fear, guilt, shame, anger, hurt, pleasure, satisfaction) to a list of automatic thoughts (AT subscale) that may occur during sexual activity. Results showed that both men and women with sexual dysfunction had significantly less positive emotional reactions to automatic thoughts during sexual activity. Sexually dysfunctional men had significantly more emotions of sadness, disillusion, and fear, and less pleasure and satisfaction, compared to men without sexual problems. Women with sexual dysfunction had significantly less pleasure and satisfaction, and more sadness, disillusion, guilt, and anger. Findings were congruent with recent studies indicating that emotions related to depressed affect (sadness, disillusion, lack of pleasure) as opposed to negative emotions (mostly related to anxiety) were stronger correlates of sexual dysfunction.